Tathbiqu Maharati al-Kalam 'ala Asasi al-Mawaqif li Thullabi al-Jami'ah - Mabrurrosi, Mabrurrosi; Ar Rozi, Rahmat Jamil; Rohman, Abd. (International Conference on Islamic Studies, 2021)
Darul Ulum Banyuanyar Islamic College was one of the new colleges that used the established curriculum. The Arabic language in the college is taught at the first level with the four language skills, which are listening, speaking, reading and writing. The researcher would like to seek in this research and focus on the types of topics that are suitable in this regard, speaking of speaking skill on the basis of situations that control their selection and arrangement, and the researcher uses the appropriate educational materials in them. This research is conducted using the development approach, Burg and Gall stated that research and development. The results of the research are: 1) Needs analysis, planning and development, material development, expert arbitration, modification and correction, field experiment, recent modifications and corrections. 2) New teaching materials are effective in improving students' ability when performing their oral expression. This appears when the researcher compared the results in the pre-test and the post-test, and that the degree of t-account (t0) in this research (93,3) is greater than the degree of t-table at the level of 99% (2.83).